The intangible resources and small firms’ multilevel performance: A partial least squares approach - Aminu, Mohammed Ibrahim; Mahmood, Rosli; Muharram, Farrah Merlinda (Canadian Center of Science and Education, 2015)
Previous literature testified the impact of both intellectual capital and entrepreneurial orientation on small firm performance, but the studies generally ignore the combined effect of such intangible resources on multilevel performance (i.e., financial and non-financial performance) which is the appropriate measurement system of performance.Hence, this study designed to address this issue by investigating the impact of such intangible resources on the aforesaid performance of 302 registered small and medium firms in Nigerian.To analyze the data, variance based structural equation model was employed using SmartPLS3.Consequently, the analysis established the empirical evidence of the positive significance effects of all dimensions of intellectual capital and entrepreneurial orientation on multilevel performance.